Dissemination of environmentally friendly appropriate technology to increase corn added value in South Bontolangkasa Village, Gowa Regency - Rahmansah; Bakhrani A. Rauf; Syafiuddin Parenrengi; Herman (LPPM Politeknik Sandi Karsa, 2026)
This community service program aimed to increase the added value of maize through the dissemination of environmentally friendly appropriate technology in Bontolangkasa Selatan Village, Bontonompo District, Gowa Regency. Although maize production in the area is relatively high, farmers predominantly sell their harvest in the form of dried kernels, resulting in low economic returns. The main problems identified included limited access to post-harvest technology, low diversification of maize-based products, weak business management, and insufficient human resource capacity. The program was implemented using a Participatory Rural Appraisal (PRA) approach to ensure active community involvement at all stages, including problem identification, planning, implementation, and evaluation. The intervention combined technology transfer, technical training, mentoring, and business management assistance. Environmentally friendly technologies introduced included maize shelling, grinding, and milling machines, accompanied by hands-on training in processing value-added products such as corn chips, popcorn, corn brownies, and roasted maize snacks. The results demonstrated a significant improvement in post-harvest efficiency, with processing time reduced from approximately 16 hours to 2 hours per quintal and production capacity increasing from ±30 kg/hour to ±100 kg/hour. Post-harvest losses decreased by up to 70%, while partner household income increased by approximately 25–30%. In addition, partners developed locally branded and packaged maize-based products and began applying simple financial record-keeping and digital marketing practices. Overall, the program contributed to strengthening local economic resilience by integrating appropriate technology with capacity building and participatory empowerment. This initiative demonstrates a sustainable model for community-based agro-processing development and can be replicated in other maize-producing rural areas